Transforming theological education : a practical handbook for integrative learning - Shaw, Perry (ICETE Series., 2014)
For several decades concern has been expressed about the need for greater integration and contextual significance in the curricular design of theological education. In addition there has been a growing awareness of the role theological schools should play in strengthening the missional vision and practice of local churches.